PENGARUH MOTIVASI DAN METODE PEMBELAJARAN TERHADAP PRESTASI BELAJAR AKUNTANSI (STUDI KASUS PADA SISWA SMK AL-AZHAR BATAM) - Rinjani, Niken; Hamta, Firdaus; Putra, Rizki Eka (Universitas Riau Kepulauan, 2015)
In a theoretical perspective, education is often understood and interpreted by diverse people, depending on their respective viewpoints and theories held. The differences of interpretation in the context of academic education is something that is commonplace, even to further enrich the human thinking and beneficial to the development of the theory itself.Motivation to learn itself as the driving force of the student / students can lead to learning and provide direction on learning activities, so that the desired goal by studying subjects that can be achieved, and the process will stimulate the learning process will tend to be more prepared and diligent in learning.In this study, entitled Effect of Motivation and Learning Methods Against Achievement in Accounting at SMK Al-Azhar Batam. The result is a table coeficient sig. Obtained 0.159 0.05, thus the motivation to learn not significantly affect the achievement of vocational study accounting at Al-Azhar Batam. From table coeficient obtained sig. 0000 where sig 0.05, thus learning method significantly affect learning achievement in vocational accounting Al-Azhar Batam. Of the value in the table obtained sig 0.000, meaning that the value of sig below 0.05. And thus, learning motivation and learning methods have a significant effect on the achievement of vocational students study accounting at Al-Azhar Batam. Keywords: Motivation, Learning Method and Learning Achievement in Accounting